DISSOLVED TRACE ELEMENTS IN RIVER WATER: SPATIAL DISTRIBUTION AND THE INFLUENCING FACTOR, A STUDY FOR THE PEARL RIVER DELTA ECONOMIC ZONE, CHINA - Ouyang T.P.; Zhu Z.Y.; Kuang Y.Q.; Huang N.S.; Tan J.J.; Guo G.Z.; Gu L.S.; Sun B. (My University, 2006)
Twenty-nine water samples were collected from different river channels of the Pearl River Delta Economic Zone, China. An inductively coupled plasma-mass spectromonitor (ICP-MS) was used to measure concentrations of the trace elements in these samples. The results suggest that the average concentrations of rare earth elements in river water show an increasing trend from the West River, the North River, the rivers of the Pearl River Delta, and the Shenzhen River to the East River. Relatively high concentrations of heavy metals appear in the East River, the rivers of the Pearl River Delta and the Shenzhen River, while the West River and the North River have relatively low heavy metal concentrations. Trace element concentrations in samples collected near urban or industrial areas are much higher than those of samples collected from distant areas, away from urban and industrial areas. After natural conditions, human activities have significant influence on the trace element concentrations in river water. This trace element concentration’s spatial distribution in the river water from the Pearl River Delta Economic Zone is actually an integrated effect of natural conditions and human activity.
Keywords: SPATIAL DISTRIBUTION; TRACE ELEMENT; RIVER WATER; THE PEARL RIVER DELTA ECONOMIC ZONE